The basal siliciclastic Silurian-Devonian Tacaratu formation of the Jatobá basin: Analysis of facies, provenance and palaeocurrents - Carvalho, Rizelda Regadas de; Neumann, Virgínio Henrique; Fambrini, Gelson Luis; Assine, Mário Luis [UNESP]; Vieira, Marcela Marques; Rocha, Dunaldson Eliézer Guedes Alcoforado da; Ramos, Germano Mário Silva (Elsevier, 2018)
The Silurian-Devonian Tacaratu Formation represents the basal siliciclastic sequence of the Jatobá Basin and is the focus of this study. Provenance and palaeocurrent studies are fundamental to the analysis and understanding of the surface diagenetic evolution and tectonic evolution of sedimentary basins. Field work (stratigraphic logs and sedimentary structures) and laboratory studies (petrography) were used for characterization this sedimentary fill. The Tacaratu Formation is comprised of sandstones varying from medium-to coarse-grained with conglomeratic levels. Seven main lithofacies have been identified and described: poorly stratified, matrix to clast-supported conglomerates; trough cross-stratified conglomerates; cross-stratified clast-supported conglomerates; cross-stratified pebbly sandstones; coarse-to medium-grained sandstones with trough cross-stratification; coarse-to medium-grained sandstones with planar cross–stratification; and horizontally stratified sandstones. The compositional analysis of 20 sandstone samples revealed homogeneity and compositional regularity among the samples. Fifty per cent of the sedimentary rocks were classified as quartz arenite, 40% as sub-litharenite, and 10% as subarkose. The provenance of these sandstones indicates a stable craton origin, with tectonic events at the margin of the basin. Diagenesis has evolved from eodiagenesis through mesodiagenesis to telodiagenesis. Palaeocurrent readings show a consistent trend to the NNW and a secondary mode to the NE. Palaeocurrent readings point to the São Francisco Craton as the main source area - more precisely the resistant areas of the Borborema Province.
Keywords: Diagenesis; Palaeocurrents; Sandstone provenance; Tacaratu formation